Signature of gene expression profile of liver sinusoidal endothelial cells in nonalcoholic steatohepatitis - Wang, Yang; Zhang, Yifan; Li, Yimin; Liu, Yun; Liu, Yulan (Frontiers in Cell and Developmental Biology, 2022)
Backgroud: There have been emerging evidence that liver sinusoidal endothelial cells (LESCs) play important role in the pathogenesis of non-alcoholic steatohepatitis (NASH). This study aims to figure out the signature of gene expression profile of LSECs in NASH, and to explore potential biomarkers related with damaged LSECs in NASH. Methods and materials: Animal experiments were performed to demonstrate the significant structural damage of LSECs in NASH model. To further understand the functional changes of these damaged LSECs in NASH, we used public GEO database that contained microarray data for the gene expression of LESCs in NASH and normal mouse liver. Differentially expressed genes (DEGs) were analysed, and further Gene Ontology (GO) Enrichment analysis were performed to understand the functional changes. The hub genes were then identified and then validated via external GEO databases. Results: There was significant structural damage of LSECs in NASH model, accompanied by remarkable functional changes of LSECs with 174 DEGs (156 upregulated and 18 downregulated genes). The functions of these DEGs were mainly enriched in the inflammatory reactions and immune responses. Nine specifically expressed hub genes were identified. Among them, CCL4 and ITGAX showed the most significant correlation with NASH, with AUROC of 0.77 and 0.86, respectively. The protein-protein interaction network, mRNA- miRNA interaction network and ceRNA network were further predicted. Conclusion: LSECs show significant structural damage and functional changes in NASH. The LSECs-related DEGs, such as CCL4 and ITGAX, might be promising biomarkers as well as potential treatment targets for NASH.